Design, user experience, and usability : Interaction design : 9th International Conference, DUXU 2020, held as part of the 22nd HCI International Conference, HCII 2020, Copenhagen, Denmark, July 19-24, 2020, Proceedings.: Interaction design : 9th International Conference, DUXU 2020, held as part of the 22nd HCI International Conference, HCII 2020, Copenhagen, Denmark, July 19-24, 2020, Proceedings. Part I (2020) - Unknown
No abstract available